Analysis of Technological Pedagogical Content Knowledge of Pancasila Education Teachers - Pinem, Sixdes Silvani; Triyanto; Nuryadi, Muhammad Hendri (International Journal of Science and Society, 2025)
This study examines how Pancasila Education teachers provide an understanding of the meaning and values of Pancasila in the topic of embodying Pancasila through the implementation of TPACK. The application of a Technological Pedagogical Content Knowledge (TPACK)-oriented learning approach is a teaching model in the field of education that encompasses the competencies teachers need to possess. Through this TPACK-oriented learning approach, teachers can perform their roles optimally and increase the likelihood of achieving educational goals, particularly in Pancasila Education. This research employs a qualitative method with a case study strategy, and the sampling technique used is purposive sampling. The number of informants in this qualitative research is determined based on the saturation of the data collected during the study. The subjects in this study consisted of two Pancasila Education teachers (G1 and G2) and 60 students from grade XI. Based on the research conducted, the findings indicate that Pancasila Education teachers at one senior high school in Surakarta City have demonstrated a good understanding of integrating technology, pedagogy, and content in the learning process.